Gluten-Free Autochthonous Foodstuff (South America and Other Countries) - Garcia, Maria Alejandra (2015)
The conservation and sustainable use of biodiversity for agricultureand nutrition have been extensively pointed out as crucial elements forfood security and nutrition. Likewise, the relevance of learning fromtraditional foods and applying indigenous knowledge for thedevelopment and production of innovative gluten-free foods has beenreferred.South and Central America have supplied a great quantity of plantfoods for the sustenance of the humankind. Latin-America is by thistime one of the World largest net food exporting area. However, itscomplete potential to expand agricultural production for regionalconsumption and global export has not yet been achieved. The regionhas a large number of skilled farmers that have preserved andtransmitted their knowledge through generations.Feeding a rapidly growing global population without expandingfarming into environmentally susceptible areas and reducing theproductive ability of the land already cultivated is a challenge thatpresents an elevated complexity level.In a framework of a strong need for diet diversification, populationswith special nutritional requirements, such as celiac patients, should bebenefited with the offer of more balanced, rich and safe dietcomponents. The possibility of learning to a great extent fromtraditional foods and spread on local and territorial knowledge for thedevelopment and production of innovative gluten-free foods appears asa promising alternative.This chapter collects information about several plant species fromthe American continent that are more extensively used for the production of gluten-free foods (e. g. maize, potato, cassava, sweetpotato, quinoa, amaranth, some legume grains) as well as other speciesthat could potentially be developed with the same purpose, such as theAndean root and tuber crops: achira, ahipa, arracacha, maca, mashua,mauka, oca, ulluco, and yacon.